Foliar Application of Amino Acids Increases Sweet Basil (Ocimum basilicum L.) Resistance to High-Temperature Stress - Justina Deveikytė; Aušra Blinstrubienė; Natalija Burbulis; Aldona Baltušnikienė (Plants)
Climate change poses a significant threat to food security, with projections indicating a decline in crop yield due to reduced crop growth in the face of rising temperatures. This study evaluated the effects of L-Isoleucine, L-Methionine, L-Glutamine, L-Tryptophan, and L-Phenylalanine on the morphophysiological parameters, total phenolic content, and antioxidant activity of Sweet Basil (Ocimum basilicum L.) under high-temperature stress. Ten cultivar varieties of the sweet basil, “Rosie”, “Red Opal”, “Bordeaux”, “Dark Opal”, “Red Rubin”, “Genovese”, “Cinamon”, “Italiano Classico”, “Marseillais”, and “Thai”, were grown in a controlled-environment growth chamber. The seedlings with 5–6 true leaves were divided into seven groups: the first group of seedlings had no treatment and was grown under 25/22 °C (day/night) temperature, the second group of seedlings had no treatment and was grown under 35/30 °C (day/night) temperature, and the remaining five groups were sprayed with 100 mg L−1 of L-Isoleucine, L-Methionine, L-Glutamine, L-Tryptophan, or L-Phenylalanine. As our results show, L-Tryptophan increased fresh and dry biomass in green sweet basil, while L-Methionine had the greatest effect on biomass in purple varieties. L-Phenylalanine increased chlorophyll a and b in heat-stressed “Bordeaux” (purple variety) and “Marseillais” (green variety). L-Isoleucine and L-Glutamine increased total phenolic compounds (TPCs) in purple cultivars (“Rosie”, “Red Opal”, “Dark Opal”, and “Red Rubin”), while L-Tryptophan (“Cinamon” and “Italiano Classico”) and L-Phenylalanine increased TPCs in “Cinamon”, “Marseillais”, and “Thai” green cultivars. Antioxidant activity (ABTS) was highest in “Dark Opal” and “Bordeaux” treated with L-Tryptophan or L-Phenylalanine under heat stress, while “Thai” benefited most from L-Isoleucine. The exogenous application of amino acids could serve as a viable solution to alleviate the negative effects of temperature stress on sweet basil and serve as an environmentally friendly agricultural strategy.